PERAN INTERNATIONAL LABOUR ORGANIZATION (ILO) DALAM MELINDUNGI BURUH MIGRAN INDONESIA DI ARAB SAUDI TAHUN 2012-2016 - Valensy, Cici; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study is a contemporary study that discusses International Labour Organization (ILO) The Role in Protecting Indonesian Migrant Workers in Saudi Arabia 2012-2016. This study aims to identify and explain the role of the ILO in protecting the rights of Indonesian migrant workers in Saudi Arabia. Indonesia is one of the largest sending countries of Indonesian migrant workers in the world. Where Indonesian migrant workers become the second largest foreign exchange earner for the country after oil and gas sector (oil and gas). The presence of Indonesian migrant workers who work abroad on the one hand has a negative impact, where the number of Indonesian migrant workers who received unjust treatment and human rights violations. Saudi Arabia became the country most experienced problems of Indonesian migrant workers.ILO an organization under the auspices of the United Nations (UN) agency that manages the field of employment in the international world. The ILO is responsible for promoting workplace rights, encouraging the creation of decent work, enhancing social protection and strengthening dialogue on labor-related issues.In solving the problems of ILO migrant workers in cooperation with Indonesia, drafting migrant conventions of migrant workers, conducting programs and campaigns related to migrant workers.In this case the authors use perpective pluralism, which is supported by the theory of international organizations and the concept of role and level of group analysis, as the actor. The concept leads to qualitative methods and literature studies as a source of information.Keywords: Role, International Labour Organization (ILO), Indonesian migrant workers, Saudi Arabia